The inclusive didactic action of the teacher: towards a fair and sustainable post-Covid-19 school - Gulisano, Daniela (Formazione & insegnamento, 2021)
The long path that is being led towards an inclusive school model increasingly able to accommodate all students, responding to the diversified needs of each of them, has been stimulated and accompanied by specific national regulatory provisions, as well as by declarations from prestigious organizations international. In this perspective, the teacher certainly plays a central role, called to operate in an educational context characterized by profound changes, accentuated by the crisis triggered by the Covid-19 pandemic, which has called for a substantial renewal of teaching and inclusive and planning processes. . In this new perspective, with the “special normality” as a starting point, teachers are required to make an educational investment that is increasingly capable of innovating and differentiating teaching strategies in a creative and flexible way, to make them not only more suitable for the present age, but above all significant for the needs of each one, with constant solicitude and attention to personal characteristics and individual needs, so that the potential of all can emerge and mature. To this end, in this contribution the Author analyzes the fundamental elements that make up teacher training in an inclusive perspective and its action, in the light of the many changes that distinguish the school of the third millennium.